El campamento “Pitral Lauquen” ranqueles prisioneros de la 3a División Expedicionaria (1879) - Pérez Zavala, Graciana (EDITORIAL DE LA UNIVERSIDAD NACIONAL DEL SUR, 2021)
At the end of the 1870s, the oppressive policies of the Argentine State were intensified towards the indigenous people linked to the Southern Border, visible in the punitive expeditions of 1878-1879. In the case of the ranqueles, located in the central Pampa, these actions were part of previous strategies of attrition, carried out by the military commanders of San Luis and Córdoba through the diplomatic channel, softening campaigns and co-optation of contingents who, both forced and voluntarily, migrated to the forts Villa Mercedes and Sarmiento. From a line of investigation that seeks to reconstruct the itineraries of the ranqueles submitted in the aforementioned context, the article characterizes the imprisonment of the indigenous people taken by the 3rd Expeditionary Division (April-August 1879) under the leadership of Colonel Eduardo Racedo. Its purpose is to describe their living conditions while they were in the Pitral Lauquen camp (near Poitagué), understanding that it simultaneously acted as a place of concentration and distribution of prisoners.